2012
DOI: 10.1097/sap.0b013e318212f39a
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Study of the Surgical Management of Panniculitis

Abstract: Patients with panniculus morbidus have an abdominal panniculus that becomes a pathologic entity, associated with the development of candidal intertrigo, dermatitis, lymphedema, and ischemic panniculitis. Panniculectomy is a standard treatment for this problem. The objective of this study was to determine risk factors for complications associated with panniculectomy surgery to lower the complication rate. We performed a retrospective chart review of patients who underwent panniculectomy between 1999 and 2007 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
1
18
0
3
Order By: Relevance
“…Those with a body mass index greater than 60 were 15.5 times more likely to have a wound complication. 9 Panniculectomy combined with other operations has shown increased complication rates, similar to those reported in various studies. [10][11][12][13] The wound complications in our patients presented in various forms, including seroma, fat necrosis, and primary dehiscence, and some of these had an associated infection or bacterial growth.…”
Section: Discussionsupporting
confidence: 77%
“…Those with a body mass index greater than 60 were 15.5 times more likely to have a wound complication. 9 Panniculectomy combined with other operations has shown increased complication rates, similar to those reported in various studies. [10][11][12][13] The wound complications in our patients presented in various forms, including seroma, fat necrosis, and primary dehiscence, and some of these had an associated infection or bacterial growth.…”
Section: Discussionsupporting
confidence: 77%
“…In those studies, complication rates ranged from 33 to greater than 45%, and operative reintervention rates from 11 to 20%. [13][14][15] Importantly, the perioperative risk profile of our patient cohort---compared with all of the aforementioned studies' cohorts---appears to differ substantially: for instance, the proportion of diabetic patients in these studies was less than 20% (vs 70% in the present study), and the incidence of CKD V was not reported (and is therefore assumed to be very low or even close to 0% [vs 100% in our study]). [10][11][12][13][14][15] Hence, a direct comparison of our outcomes with these previous reports is difficult, because diabetes and CKD stage have a substantial adverse impact on wound and other complication rates after abdominal operative procedures.…”
Section: Surgery J 2015mentioning
confidence: 63%
“…demuestran una correlación estadísticamente significativa entre el tamaño del faldón abdominal o tener un IMC mayor de 39 kg/m 2 con las complicaciones de la herida 9,10 . Por otro lado, se producen alteraciones hidroelectrolíticas y pérdidas sanguíneas que incrementan las necesidades de transfusión, y hay descritos casos de muerte por tromboembolismo, sepsis o infarto agudo de miocardio 3 .…”
Section: Figura 4 -Resultado Posoperatorio a Los 6 Meses De La Panicuunclassified